1984
DOI: 10.1002/ajim.4700060606
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of self‐reported regulatory data: The case of coal mine dust

Abstract: Coal-mine owners are required to measure miner exposures to respirable dust so that compliance with Federal health regulations can be monitored. This study analyzes the problem of possible underreporting of dust exposures. Using two statistical approaches, data for three mining occupations in 54 large underground coal mines during 1976-1978 are examined for evidence of underreporting. First, regression estimates compare dust concentrations reported by coal-mine owners with those reported by government health i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…We used MSHA compliance dust concentration data. It is important to note as a limitation that the validity of these data has been periodically questioned 11 21. However, if any bias present in the exposure data is systematic and non-differential with respect to MSHA district, the internal associations we present should be unaffected.…”
Section: Discussionmentioning
confidence: 90%
“…We used MSHA compliance dust concentration data. It is important to note as a limitation that the validity of these data has been periodically questioned 11 21. However, if any bias present in the exposure data is systematic and non-differential with respect to MSHA district, the internal associations we present should be unaffected.…”
Section: Discussionmentioning
confidence: 90%
“…This again provides incentives to underreport. Research presented to MSHA in 1983, published in 1984, and confirmed in 1990 clearly demonstrated substantial under-reporting [Boden and Gold 1984;Seixas et al, 19901. MSHA ignored these findings (possibly because the low reported concentrations made the agency look more effective) until presented with evidence of blatant tampering in 1991.…”
Section: Unintended Consequences Of Public Policiesmentioning
confidence: 90%
“…Statistical comparison of operator and MSHA samples also reveals a systematic bias. Boden and Gold [1984] demonstrated that low weight samples (less than 0 . 3 mg/m3) were significantly and consistently more frequent in operator measurements than they were in MSHA measurements.…”
Section: Additional Evidence For Biasmentioning
confidence: 98%